The Quality Management of New Product Design and Development - Wang, H. M. (Cranfield University, 1993)
The quality management of a modern complex product from design to production is very complicated matter which involves the whole company as well as external bodies (customer and supplier etc). In this thesis, based on customer-oriented principles, major management techniques, creating a time phased quality management programme to approach the quality related design processes, combines with the development of a quantitative method to measure the quality achievement of each design activity, including each phase and the overall design stage, for their correctness and efficiency in terms of time, cost and performance. A practical example is given for demonstrating the validation of the quantification. Through proper tailoring, the time phased quality management programme can be applied to different types of product, simple and complex, and to hardware and software, as well as to totally new design or partial design improvement. A quality information system is also developed to enhance the efficiency and effectiveness of the design and development process and to obtain improved product performance. Through a systematic analysis of the design process, it is shown that the majority of the steps taken are amenable to discipline and control and, therefore, design can realistically be included in a formal quality management system.